Pengembangan Sistem Informasi Biro Perjalanan Wisata berbasis Web menggunakan Payment Gateway dan Booking Paket Wisata (Studi Kasus: CV. Maha Cipta Wisata) - Adi Maulana Rifa'i; Bayu Rahayudi; Dwija Wisnu Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Tourism is a field that has bright business prospects, this can be seen by the increasing number of foreign and domestic tourists visiting many tourist objects in Indonesia. CV. Maha Cipta Wisata is a company engaged in tour & travel. provides various types of tourism packages, industrial visits, family gatherings, hotels, and buses. However, conventional hotel sales and marketing method is by ordering and paying via whatsapp. The transaction creates a loophole, because it can allow errors in uploading payments and must be checked for validation first by the admin. Based on the existing problems, a dynamic web-based tour package booking information system is needed that has payment gateways. It is hoped that with this integration, consumers can choose many payment method options and can increase consumer confidence because facilitator in making payments. Method of developing an information system using prototype is a development that saves time and costs without compromising product quality. While at the implementation stage using Laravel framework. Results of the development of a web-based travel agency information system using payment gateways and booking tour packages (case : CV. Maha Cipta Wisata) can help manage sales such as hotels and tour packages, in addition to the existence of a payment gateway providing various payment methods so that consumers get freedom in choosing payment methods. And black box testing is 100% valid. while compatibility using the sortsite works well.